Reducing Quality Costs Through the Integration of Six Sigma, Process Failure Mode And Effects Analysis (PFMEA), and Theory of Inventive Problem Solving (TRIZ) in Mass Production Electronics Manufacturing - Laksmi, Divyah; Suparno, Suparno (International Journal Labs, 2025)
This thesis proposal outlines a study aimed at reducing quality costs through the integration of Six Sigma, Process Failure Mode and Effects Analysis (PFMEA), and the Theory of Inventive Problem Solving (TRIZ) within the context of electronics manufacturing at PT X. NQC, which refers to costs incurred from products failing to meet established quality standards, has emerged as a critical concern for the company due to its substantial impact on overall expenditures. The primary objective of this research is to identify the underlying factors contributing to elevated NQC and to develop effective solutions through a comprehensive, integrated approach. The research methodology will encompass a thorough analysis of the production process, the identification of potential failure modes, and the application of TRIZ methodology to reduce subjectivity in the PFMEA analysis. By synthesizing these three methodologies, it is anticipated that actionable recommendations will be generated to improve product quality and enhance operational efficiency. This research is expected to yield practical solutions for PT X while also contributing to the advancement of theories and practices in quality management within the manufacturing sector. The outcomes of this study will serve as a valuable reference for other organizations encountering similar challenges in their efforts to enhance quality and cost efficiency.